APPLICATION OF RAIL-BASED URBAN PUBLIC TRANSPORTATION IN THE METROPOLITAN AREA OF PATUNGRAYA AGUNG - Muhammad Alfat Rizki Pratama; Dhea Jaen; Ilham Ziaulhaq; Muhammad Ali Hanafiah (Jurnal Scientia, 2023)
The development of the urban transportation system is inseparable from the increase in private vehicle ownership which makes the vehicle movement so high, especially in urban areas that can cause problems in the future. This research aims to create a rail-based urban public transportation system in Patungraya Agung Metropolitan Area. This study uses qualitative methods, with data collection techniques using observation and literature study. The analysis is carried out by considering traffic movements and adjustments to existing spatial planning. The study results show that the movement level is generally within Palembang. So that it is planned to have 8 coridor in the scenario of developing a rail-based public transportation system in Patungraya Agung Area. Location of the station which was developed using the TOD concept, so that the location of the station is close to the center of activity. Corridors P2, P3, P4, P5, and P6 (within cities) are developed by elevated using Light Rail Transit, while corridors 1, 2 and 3 are developed on ground using inter-city Commuter Lines.